2012
DOI: 10.1177/1545109712463733
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Treatment Switch for Virologic Failure during First-Line Antiretroviral Therapy in Resource-Limited Settings

Abstract: We evaluated adult Nigerian patients with antiretroviral switch to second-line treatment with protease inhibitor (PI/r)-based regimens due to virologic failure (confirmed HIV-1 RNA viral load >1000 copies/mL) during first-line antiretroviral therapy. Proportion of patients with viral load (VL) >400 copies/mL and characteristics associated with non-suppression during second-line treatment are described. Approximately 15% of patients (34/225) had VL >400 copies/mL at 1-year after treatment switch to PI/r-based r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…However, due to the discrepant results, we are unable to conclude that switch to PI-based therapy alone, will lead to viral suppression. Given the high rates of transmitted and acquired NNRTI resistance among children on ART, it is possible switching to second line while also providing enhanced adherence counseling and monitoring, facilitated these children to achieve viral suppression [ 15 , 36 , 38 , 39 ]. (We were unable to detect associations between self-reported adherence, missed visits, or CD4 count on virologic failure highlighting the importance of routine VL testing to identify children in need of intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the discrepant results, we are unable to conclude that switch to PI-based therapy alone, will lead to viral suppression. Given the high rates of transmitted and acquired NNRTI resistance among children on ART, it is possible switching to second line while also providing enhanced adherence counseling and monitoring, facilitated these children to achieve viral suppression [ 15 , 36 , 38 , 39 ]. (We were unable to detect associations between self-reported adherence, missed visits, or CD4 count on virologic failure highlighting the importance of routine VL testing to identify children in need of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This is well below the rate of suppression found for adults in low- and middle-income countries (LMICs) (85%) in a similar systematic review, and far below the rate for children in high income countries (90%). Prolonged treatment with a failed regimen can lead to increased drug resistance [ 13 , 14 ], higher viral load and increased risk of failing second line therapy [ 15 ]. Conversely, premature switching without confirmation of virologic failure limits treatment options and leads to unnecessary increases in cost.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal adherence (i.e., missing of any dose in the past 3 days [22] or 7 days [23]; or less than 95% adherence in the past 30 days [24] or less than 90% adherence in the past year [25]) was indicated as a key determinant of second-line HIV treatment failure [26, 27]. Suboptimal adherence could be a result of regimen toxicities [28].…”
Section: Introductionmentioning
confidence: 99%
“…Following removal of duplicates, we screened 3525 abstracts and selected 206 full articles for review; the selection showed good agreement between reviewers (Cohen κ = 0.70 [95% CI, .63–.76]). Twenty articles describing 15 studies met the inclusion criteria ( Figure 1 ), comprising 5 RCTs [ 6 , 13–18 ], 5 prospective observational studies [ 19–25 ], and 5 retrospective observational studies [ 26–31 ]. Six studies were reported from multinational cohorts [ 13–17 , 19 , 23 ].…”
Section: Resultsmentioning
confidence: 99%